Integrating OLabs in Problem-Based Hybrid Learning: Effects on Higher Order Thinking Skills - Rahma, Putri Haliza; Maulidah, Rifa'atul; Makiyah, Yanti Sofi (Jurnal Pendidikan Fisika, 2025)
This study was motivated by the low levels of student engagement and higher-order thinking skills (HOTS) observed in a preliminary investigation at State High School 1 Talaga, exacerbated by limited laboratory resources that hindered effective learning. The research aimed to explore the effect of a Problem-Based Hybrid Learning (Pro-BHL) model, supported by OLabs (Online Laboratory), on improving students' HOTS, specifically in the topics of heat and heat transfer. A quasi-experimental design with a posttest-only control group was implemented, involving 244 students from 7 classes. Through purposive sampling, the study selected class XI MIPA 3 as the experimental group and XI MIPA 2 as the control group. HOTS was measured via an essay-based posttest, addressing analysis (C4), evaluation (C5), and creation (C6) indicators. The results, analyzed using a t-test at a significance level of α = 0.05, revealed a statistically significant improvement in the experimental group’s HOTS (tcount = 6.65 ttable = 1.67), rejecting the null hypothesis and confirming the effectiveness of the Pro-BHL model supported by OLabs. The findings indicate that this hybrid learning model significantly enhanced students' higher-order thinking skills in the studied topics. The research highlights the potential of integrating technology like OLabs into problem-based learning frameworks, providing a scalable solution to overcome practical limitations in science education. Future research could explore integrating other virtual laboratory platforms and extending the model to different learning environments.